Cysts reabsorption in the testis of the bee wax pest Achroia grisella (Lepidoptera, Pyralidae) during spermatogenesis - Fernandez, F. C. [UNESP]; Da Cruz-Landim, C. [UNESP] (My University, 2004)
The present paper reports the occurrence of testicular cysts degeneration during spermatogenesis of Achroia grisella, a Lepidoptera with dimorphic spermatogenesis, through ultrastrucutural studies. Signs of cysts degeneration can be detected in the last larval instar but it increases during pupation and early adulthood. The degeneration affects the eupyrene, as well apyrene cysts but it is not always possible to recognize which cysts are degenerating. Some morphological features of cysts degeneration resemble apoptosis.
Keywords: Apoptosis; Apyrene; Cyst degeneration; Eupyrene; Spermiogenesis; Apoidea; Lepidoptera; Propolis; Pyralidae